Teaching Practice Program in College of Education – Creativity, Emotional Intelligence and Locus of Control - Hutabarat, Zuhri Saputra; Riady, Yasir; Amral, Sainil; Sumiharti, Sumiharti; Susanti, Heni; Saputra, Trio; Affrian, Reno; Taufan, Ade (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to analyze the ability of prospective teachers to prepare themselves to become real teachers through creativity, emotional intelligence, and locus of control. The approach used in this research was quantitative research with a survey model research design with a population of 755 and a sample of 261 economic education students who have completed the teaching practice program. Exploratory factor analysis, confirmatory factor analysis, and a structural equation model were used to evaluate the data. The study's findings included the following: first, aspiring teachers were innovative in their use of and development of original learning methods, models, and media so that they are easily understood by students and can be used by future teachers to teach correctly, effectively, and efficiently to boost student motivation. Second, prospective teachers could maximize their potential with mature emotional intelligence when teaching practice programs. Third, the embodiment of confidence about the self-efficacy of future teachers in implementing teaching practice programs caused their potential to increase so that they could be channeled properly, as evidenced when interacting with students in delivering subject matter at school. The results of this study confirm that overall, the six hypotheses have a positive and significant effect; through teaching and learning activities and other teacher responsibilities at higher education schools, prospective instructors can demonstrate their performance in realistic scenarios.